2017
DOI: 10.2147/ijn.s141272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial, angiogenic, and osteogenic activities of green synthesized gap-bridging copper-doped nanocomposite coatings

Abstract: Titanium (Ti) and its alloys have been widely used in clinics for years. However, their bio-inert surface challenges application in patients with compromised surgical conditions. Numerous studies were conducted to modify the surface topography and chemical composition of Ti substrates, for the purpose of obtaining antibacterial, angiogenic, and osteogenic activities. In this study, using green electrophoretic deposition method, we fabricated gap-bridging chitosan-gelatin (CSG) nanocomposite coatings incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Other groups have developed multifunctional coppercontaining particles; for example Huang et al (2017) have modified the surface of titanium implants with a chitosan-gelatin nanocomposite containing Cu ions. These composites also have antibacterial and proangiogenic properties, however there are limitations with respect to the usage since they are linked to titanium.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have developed multifunctional coppercontaining particles; for example Huang et al (2017) have modified the surface of titanium implants with a chitosan-gelatin nanocomposite containing Cu ions. These composites also have antibacterial and proangiogenic properties, however there are limitations with respect to the usage since they are linked to titanium.…”
Section: Discussionmentioning
confidence: 99%
“…The next stage of copper toxicity to bacteria was the effect on ROS overproduction, suppression of cellular respiration, and the effect on gene replication. Huang et al [98] performed similar studies using different concentrations of Cu (from 0.01 to 10 mM). The results of these studies have shown that the most preferred concentration of Cu in the composition of Cu-Ti film was about 1 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Swelling characteristic of Cu(II)-CS coatings was determined by immersing the coated specimens into 10 mL phosphate buffered saline (PBS) solution for 1,3,7,10,15,20,25,30,40,50,60,90, and 120 min. The swelling ratio was determined according to the following formula:…”
Section: Swelling Ratiomentioning
confidence: 99%
“…According to the literature, there have been few attempts to co-deposit CS with various TMIs by EPD, using a simultaneous cathodic deposition. However, the results from such previous studies indicate that atomic deposition of the metallic phase and the formation of new crystalline phases occur on the electrode after EPD [10,[24][25][26][27]. In such cases metal particles physically embedded in the chitosan matrix and furthermore the addition of salts in the deposition suspension significantly effects CS electrodeposition behavior, which leads to the formation of less homogeneous and less rigid films [28,29].…”
Section: Introductionmentioning
confidence: 99%